Evaluating the tourism appeal of traditional craft villages in Vietnam: A case study from the tourists’ perspective in Thanh Hóa province - Hung, Nguyen Thi Viet; Ha, Nguyen Thi; Thuc, Nguyen Thi; Huong, Nguyen Thi Lan (Edelweiss Applied Science and Technology, 2025)
Developing tourism in traditional craft villages is a promising direction and has been prioritized by Southeast Asian countries in their tourism promotion and development policies. The significant benefits of integrating traditional craft villages into the tourism value chain are evident not only in economic growth, job creation, and increased income for local residents, but more importantly, in preserving cultural heritage effectively. In Vietnam, the development of tourism in traditional craft villages has often been discussed from perspectives such as planning and investment, village value, or livelihood within the village. Meanwhile, viewing this issue from the demand side—tourist preferences and choices—when developing tourism in traditional craft destinations appears to be a practical yet underexplored approach. This is precisely the focus of this article, which draws from survey data and analyzes a specific, relatively typical case study in Thanh Hóa province, Vietnam—a province with many traditional craft villages and an emerging destination for this form of tourism.